# Talk:Equality implies Substitution

Jump to navigation
Jump to search

The statement is a theorem. It is the predicate logic statement:

- $( \exists x: P(x) \land \forall y: ( P(y) \implies Q(y) ) ) \implies \exists x: ( P(x) \land Q(x) )$ --Andrew Salmon 19:16, 11 August 2012 (UTC)

- Okay, then it needs justification/proof. --GFauxPas 20:37, 11 August 2012 (UTC)

- Yup...but unfortunately, the predicate logic section is a little lacking. --Andrew Salmon 21:17, 11 August 2012 (UTC)

- It's on my list... somewhere at the bottom. --Lord_Farin 21:21, 11 August 2012 (UTC)

I see your comment about "needs purging" -- but I'd be interested to read Quine to see how he justifies this treatment first ... must put it on my xmas list. --prime mover (talk) 20:54, 3 November 2014 (UTC)